2002
DOI: 10.1260/026361702321705285
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Emission of Ammonia through Adsorption in a Fixed Bed of Activated Carbon

Abstract: ABSTRACT:The increase in atmospheric pollution caused by polluting gases has made it necessary to conduct studies aimed at decreasing or treating the emissions of such gases. Due to its increasing presence in the atmosphere, ammonia is one of the most pre-eminent of these. The present work studied the control of the emission of this gas through its adsorption in a fixed bed of activated carbon. The results showed that the adsorption capacity increased from approximately 0.2 to 1.9 mg NH 3 /g carbon as the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Palm oil shell char (generated at 500 • C) had an NH 3 adsorption capacity, q, similar to untreated activated carbon and ranged from 0.70 to 0.95 mg g −1 for 6-14 ppmv NH 3 (23 • C). These results are similar to NH 3 adsorption studies using untreated activated carbon from coconut shells (480 m 2 g −1 ) in which q ranged from 0.6 to 1.8 mg g −1 from 600 to 2400 ppmv NH 3 at 40 • C [5] (Table 3). However, our reported NH 3 adsorption capacities for the untreated carbon were significantly lower than activated carbon from palm-shells via acid oxidation or CO 2 activation (70-130 mg g −1 for 2000 ppmv NH 3 at 50 • C- [14,15] (Table 3).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Palm oil shell char (generated at 500 • C) had an NH 3 adsorption capacity, q, similar to untreated activated carbon and ranged from 0.70 to 0.95 mg g −1 for 6-14 ppmv NH 3 (23 • C). These results are similar to NH 3 adsorption studies using untreated activated carbon from coconut shells (480 m 2 g −1 ) in which q ranged from 0.6 to 1.8 mg g −1 from 600 to 2400 ppmv NH 3 at 40 • C [5] (Table 3). However, our reported NH 3 adsorption capacities for the untreated carbon were significantly lower than activated carbon from palm-shells via acid oxidation or CO 2 activation (70-130 mg g −1 for 2000 ppmv NH 3 at 50 • C- [14,15] (Table 3).…”
Section: Discussionsupporting
confidence: 84%
“…The physical and chemical characteristics of the wood fly ash, including pH, surface area, bulk density, and the elemental composition were previously determined [22] and are reported in Table 1. The poultry litter ash was not characterized, but typical physical characteristics have recently been reported [5]. Activated carbon (Darco TM granular, untreated 4-12 mesh, Sigma-Aldrich) was obtained from Sigma-Aldrich (Table 1) and used as a benchmark in this research.…”
Section: Biomass Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular example of ammonia adsorption/desorption is discussed further and it should be noted that most polar molecules behave in a similar fashion. A study by Rodrigues and Moraes [2002] found that at all temperatures the physisorption capacity of ammonia increased with increasing ammonia concentration, but an increase in temperature at any concentration led to a decrease in the adsorption capacity of ammonia. The study also concluded that the effect of temperature more significantly affected desorption than that of ammonia concentration.…”
Section: Measurement Proceduresmentioning
confidence: 96%
“…The value of sensor response to both gases was maximal at 40 • C, however further temperature growth led to its decrease compared to that measured at room temperature. This behavior appears to be due to two competing processes, namely an increase of desorption [74] and growth of the concentration of charge carriers in p-type semiconductors with temperature [75]. Different rate of desorption of the chemisorbed oxygen from the surface of hybrid material at different temperatures may also contribute to these processes.…”
Section: Effect Of Operating Temperaturementioning
confidence: 99%